Dynamical boundary value problem for a viscoelastic half-space with cut - Shavlakadze, Nugzar; Odishelidze, Nana; Pachulia, Bachuki; Criado-Aldeanueva, Francisco (Springer Nature, 2025)
The dynamical boundary value problem for viscoelastic half-space with cut in the form of a strip is considered. The problem is reduced to the singular integral equation of ﬁrst kind. Using the method of orthogonal polynomials, the integral equation is reduced to an inﬁnite system of linear algebraic equations. The quasi-completely regularity of the obtained system is proved and the reduction method for approximate solution is developed.
Keywords: Física aplicada; Dynamical boundary